2020 International Joint Conference on Neural Networks (IJCNN) 2020
DOI: 10.1109/ijcnn48605.2020.9206872
|View full text |Cite
|
Sign up to set email alerts
|

Hyperparameter Optimization in Binary Communication Networks for Neuromorphic Deployment

Abstract: Training neural networks for neuromorphic deployment is non-trivial. There have been a variety of approaches proposed to adapt back-propagation or back-propagation-like algorithms appropriate for training. Considering that these networks often have very different performance characteristics than traditional neural networks, it is often unclear how to set either the network topology or the hyperparameters to achieve optimal performance. In this work, we introduce a Bayesian approach for optimizing the hyperpara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Various techniques proposed for training spiking neural networks with different underlying hardware, are vital steps toward efficient neuromorphic computing for edge devices; however, each of these approaches require several hyperparameters and their optimum performance depend on prior knowledge on how to set these hyperparameters. In Parsa et al (2020), we showed that an optimum set of hyperparameters drastically increases the neuromorphic system performance.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Various techniques proposed for training spiking neural networks with different underlying hardware, are vital steps toward efficient neuromorphic computing for edge devices; however, each of these approaches require several hyperparameters and their optimum performance depend on prior knowledge on how to set these hyperparameters. In Parsa et al (2020), we showed that an optimum set of hyperparameters drastically increases the neuromorphic system performance.…”
Section: Background and Related Workmentioning
confidence: 99%